PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PERSONEL POLRES PAMEKASAN MELALUI KEMAMPUAN KERJA - Chamariyah; Mohammad Rofiq Hariyadi; C. Sri Hartati (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The results of the research show that: 1) Work discipline has a direct significant effect on personnel performance with the original sample value of 0.302; 2) Motivation has a significant direct effect on personnel performance with the original sample value of 0.157; 3) Work Discipline has a direct significant effect on work ability with the original sample value of 0.455; 4) Motivation has a significant positive direct effect on work ability with the original sample value of 0.267; 5) Work ability has a direct significant effect on personnel performance with the original sample value of 0.267; 6) Work Discipline has an indirect significant effect on personnel performance mediated by work ability with an original sample value of 0.175; 7) Motivation has a significant indirect effect on personnel performance mediated by work ability with an original sample value of 0.103;